Understanding the ‘other’: the case of Al-Biruni (973-1048 AD) - Senin, Nurhanisah; Grine, Fadila; Wan Ramli, Wan Adli; Mohd Khambali @ Hambali, Khadijah; Ramlan, Siti Fairuz (Emerald, 2019)
Purpose: This study aims to demonstrate al-Biruni’s originality in the study of religion and the exploration of religious truth, while his firm stance on his religion effectively advocated his need to understand others more accurately. Design/methodology/approach: This study is a review of al-Biruni’s literature that uses content analysis method in establishing al-Biruni’s approach in understanding other religions through three main methodologies. From these approaches, this paper advocates al-Biruni’s firm stance toward his own faith despite using a scientific study on Hindu, which is in contrary to other phenomenological scholars who find that religious truth is relative in nature. Findings: Al-Biruni’s methods have proven that researchers are not necessarily required to dispose off their religious identity and commitment to faith, while simultaneously achieving objectivity and accuracy. Al-Biruni’s approach to understanding others may be seen as a remarkable early model of interfaith, intercultural and inter-civilizational dialogue seeking, eventually, to promote a harmonious co-existence within a highly polarized cultural and religious context. This inquiry demonstrates al-Biruni’s scholarly depth in his attempt to harmonize his methodology with the study of religious phenomena in compliance with Islam. Originality/value: This study signifies al-Biruni’s intellectual background with his mastery of first-hand information as a solid basis and grounds for the effective understanding of others in a descriptive, systematic and comparative manner. This paper also signifies al-Biruni’s methods of understanding others without having to dispose off one’s religious identity and commitment to faith which could be exemplified by other religious scholars. © 2019, Emerald Publishing Limited.